Inhibitory effects of diarsenic trioxide (As2O3) on hepatocellular carcinoma cells exerted by regulation of promyelocytic leukemia protein levels (Bioscience Journal, 2023)
Previous Chinese research revealed that diarsenic trioxide (As2O3) inhibits acute promyelocytic leukemia (PML) cell proliferation and initiates apoptosis through degradation of the PML-retinoic acid receptor protein. This study was to analyse whether As2O3 also had an effect on hepatocellular carcinoma (HCC) cells. As2O3 effects on various HCC cell lines and primary HCC cells were investigated in time and dose series, including measurements of cell growth, PML mRNA and protein expression, xenografted tumor formation, and the self-renewal Oct4 and hepatocyte marker expressions in mouse model xenografts or cells treated with PML siRNA. The results were analyzed by immunocytochemistry, quantitative reverse transcription PCR and western blotting as well as indocyanine green and Periodic Acid Schiff staining. As2O3 inhibited HCC cell and HCC cell-derived xenograft tumor formation in a time-dependent manner and reduced PML protein expression in HCC cells, but had limited effects on PML mRNA levels in cell nuclei. The HCC cell line HuH7 treated with As2O3 showed a decreased expression of alpha-fetoprotein and increased expression and transcription of mature hepatocyte markers, indicating differentiation of HCC cells into hepatocytes. Cytokeratin 18 protein and mRNA levels as well as tyrosine aminotransferase and apolipoprotein B mRNA transcriptions were enhanced by As2O3 as were the numbers of indocyanine green and Periodic Acid Schiff stained cells. In addition, As2O3 downregulated the expression of Oct4. In conclusion, since As2O3 inhibited HCC cell proliferation and HCC cell-derived xenograft tumor formation it is suggested that an appropriate concentration of As2O3 might be a promising therapy to treat HCC.